LOS SISTEMAS DE APOYO EN LA TOMA DE DECISIONES - Rivera León, Félix Armando (2014)
Support Systems in Decision Making (SSD) “are interactive computer systems that help decision makers use data and models to solve unstructured problems” (Spraguey Carlson). The use of traditional tools based on application development management systems databases for strategic information for decision drawback presents of various kinds, such as extremely slow response time, difficulty or inability to express a complex query, and difficulty obtaining results that collect information from various sources